HUBUNGAN ANTARA KINERJA TUTOR DENGAN MOTIVASI BELAJAR PESERTA DIDIK - Rangga Rangga (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2010)
The purpose of this study was to know the correlation between tutuor's performance and the learner's motivation. The study was conducted at the Learning Center of Nurul Fikri in Petukangan, South Jakarta as from July through November 2008. The population covered 115 with 50 learners selected by cluster technique. The data were collected by using questionairs, observation, and document study. Employing correlation formula of Rank Spearman, the study proved the positive correlation between tutor's performance and learner's learning motivation. Besides this study also indicated the tutor's low performance in instructional process, and the tutor's poor knowledge in tutor's functions and competencies. The study also provides a set of recommendations to improve the tutor's performance.